A Study of Urodynamic Findings in Children Presenting with Urinary Tract Infection with and Without Reflux - Sharifian, Mostafa; Faghihizadeh, Samad; Ruzrokh, Mohsen; Mirshemirani, Alireza; Abdollah Gorji, Fatemeh; Musavian, Zahra (Journal of Pediatric Nephrology, 2015)
Introduction: Urinary Tract Infections (UTIs) are common in childhood and are frequently associated with abnormalities of the urinary tract. UTIs are the leading cause of morbidity in patients with neurologic bladder; this causes recurrent UTIs and Chronic Kidney Injury& Disease (CKD) that affects their quality of life. Children with UTIs are mostly neurologically intact, but may have infections as a result of a voiding dysfunction. The present study aimed to examine the relationship between occult bladder dysfunction and recurrent UTIs in our patients. Material and Methods: A cross-sectional study was done on 210 children aged 10 months to 15 years presenting with UTI with/without reflux who were admitted to the Nephrology Ward of Mofid Children’s Hospital between April 2011 and September 2013 using convenient sampling. Statistic analyses were conducted using descriptive statistics, Kolmogorov-Smirnov test, Mann Whitney test, Fisher’s Exact test, and odds ratio, and p values <0.05 were considered significant. Results: Of 210 Children 74% were female and 26% were male. 25% had one, 25% had two, 31% had 3, and 19% had more than 3 episodes of UTI. Eighty percent of the female and 56% of the male children had recurrent UTI (P: 0.004, odds ratio: 0.361). Fifty eight percent of the patients had Vesicoureteral Reflux which was bilateral in 34% of them. There was no correlation between UTI and Urinary Reflux (P=0.152, odds ratio=1.591) and also no correlation was detected between urodynamic findings and urinary reflux(P=0.243, odds ratio=1.485). Seventy six percent of the children with recurrent UTI had abnormal urodynamic results. Conclusions: Since many children with recurrent UTI and multiple renal scars have bladder dysfunction, it is recommended that urodynamic studies should be included in the evaluation of every child with recurrent UTI and renal scar. Keywords: Urinary Tract Infections; urodynamics; Vesico-Ureteral Reflux; Child